Fundamentals of HR analytics a manual on becoming HR analytical - Diez, Fermin 1960-; Bussin, Mark; Lee, Venessa (Bingley, UK Emerald Publishing, 2020)
aThis title provides practical, hands-on approaches to connect data to HR policies and practices to help influence overall business performance. Building on traditional HR skill sets, it makes understanding and engaging with data analytics possible for professionals at all levels. Leveraging key statistical and financial concepts, including ROI and people productivity, and commonly available tools such as Workday and Tableau, the authors explore key skills and tasks in an accessible and illuminating way, including: data-analytic thinking data management data collection clean-up and warehousing building descriptive and predictive models applying HR analytics skills and tools to workforce planning, recruitment, training, and turnover analysis.
aIncludes bibliographical references (page 247) and index.
Keywords: Personnel management; Personnel management -- Statistical methods